What Workers Need the First Day on the Job. - McNicholas, Celine; Sanders, Samantha; Shierholz, Heidi (Challenge (05775132))
A priority for the new Congress: The current legal framework in America has rolled back worker protections and contributed to the income inequality that has so undermined the economy and American values. The authors, researchers at the Economic Policy Institute, use the term First Day Fairness to argue that workers must have full rights and protections from the day they start work.